A Systematic Review of Renal Perfusion in Complex Abdominal Aortic Aneurysm Open Repair - Diletta Loschi; Enrico Rinaldi; Annarita Santoro; Nicola Favia; Nicola Galati; Germano Melissano (Journal of Cardiovascular Development and Disease, 2024)
Introduction: This systematic review aims to analyze the current literature regarding 30-day mortality and postoperative acute kidney disease (AKI) in complex abdominal aortic aneurysms (cAAAs), which included juxtarenal aortic aneurysm (JAA), suprarenal aortic aneurysm (SRAA), and type IV thoracoabdominal aortic aneurysm (TAAA) open surgery (OS), to evaluate the impact of renal perfusion on AKI and to try to define which is the best way to perform it. Methods: A literature search in PubMed and Cochrane Library was performed, and articles published from January 1986 to January 2024 reporting on JAA, SRAA, and TAAA type IV open surgery management were identified. Multicenter studies, single-center series, and case series with ≥10 patients were considered eligible. Comparisons of outcomes of patients who underwent OS for complex abdominal aortic aneurysms (cAAAs) with or without perfusion of the renal arteries were analyzed when available. The titles, abstracts, and full texts were evaluated by two authors independently. The primary outcomes included AKI and 30-day mortality rates. The new-onset dialysis rate was considered a secondary outcome. Results: A total of 295 articles were evaluated, and 21 were included, totaling 5708 patients treated for cAAAs with OS. The male patients totaled 4094 (71.7%), with a mean age of 70.35 ± 8.01 and a mean renal ischemia time of 32.14 ± 12.89 min. Data were collected and analyzed, at first in the entire cohort and then divided into two groups (no perfusion of the renal arteries—group A vs. selective perfusion—group B), with 2516 patients (44.08%) who underwent cAAAs OS without perfusion of the renal arteries and 3192 patients (55.92%) with perfusion. In group B, four types of renal perfusion were reported. Among the 21 studies included, 10 reported on selective renal perfusion in cAAA OS, with several types of fluids described: (1) “enriched” Ringer’s solution, (2) “Custodiol” (Istidine-tryptophan-ketoglutarate or Custodiol HTKsolution), (3) other cold (4 °C) solutions (i.e., several combinations of 4 °C isotonic heparinized balanced salt solution containing mannitol, sodium bicarbonate, and methylprednisolone), and (4) warm blood. Thirty-day mortality for patients in group A was 4.25% (107/2516) vs. 4.29% (137/3192) in group B. The reported incidence of AKI and new onset of dialysis was, respectively, 22.14% (557/2516) and 5.45% (137/2516) for group A and 22.49% (718/3192) and 4.32% (138/3192) for group B. A total of 579 patients presented with chronic kidney disease (CKD) at admission across all studies, which included 350 (13.91%) in group A vs. 229 (7.17%) in group B. Acute kidney injury, 30-day mortality, and new-onset dialysis rate were reported in four subgroups: (1) In the “Ringer” group, 30-day mortality was 2.52% (3/113), AKI affected 27.73% (33/119) of patients, and the new-onset dialysis rate was 2.52% (3/113). (2) In the “Custodiol” group, 30-day mortality was 3.70% (3/81), AKI affected 20.17% (24/81) of patients, and the new-onset dialysis rate was 2.46% (2/81). (3) In the “cold solutions” group (i.e., NaCl and mannitol), 30-day mortality was 4.38% (130/2966), AKI affected 21.81% (647/2966) of patients, and the new-onset dialysis rate was 4.48% (133/2966). (4) In the “Warm blood” group, 30-day mortality was 3.85% (1/26), AKI affected 53.84% (14/26) of patients, and the new-onset dialysis rate was 0% (0/26). Conclusions: This systematic review highlights the lack of standard definitions for AKI, CKD, and the type of renal perfusion. Despite similar results in terms of AKI and 30-day mortality, renal perfusion seems to be protective of the new-onset hemodialysis rate. Moreover, Custodiol appears to have lower rates of AKI and hemodialysis than the other perfusion types. A prospective randomized controlled trial to perform further subgroup analysis and research the various types of renal perfusion may be necessary to identify possible benefits.